Traumatismos Vasculares na Prática Civil - Monteiro da Silva, Antônio J.; Leite, Aldio; Araújo, Eimar; Côrtes, J. C.; Santos , Maldonat; Leal de Meirelles , Márcio; Périssé, Rodolfo; A. Rodrigues, Haroldo (Revista Brasileira de Saúde Militar, 2022)
Resumo